The open health-promoting activities programme: redefining health promotion and family dynamics by engaging parents in socioeconomically deprived Swedish communities - Lisette Farias; Mai-Lis Hellenius; Johanna Gringmann; Gisela Nyberg; Susanne Andermo (BMC Public Health)
Abstract Background Current evidence suggests that even in high-income countries such as Sweden, there are socioeconomic differences in children’s participation in physical activity. While family-based programmes appear promising to encourage physical activity, there is a lack of knowledge on how to engage families in such programmes, particularly in socioeconomically disadvantaged areas. The Open Health-Promoting Activities programme was launched to promote physical activity outdoors and health equity for children and their families in these areas. This study aims to explore parents’ experiences with the Open Health-Promoting Activities programme in socioeconomically disadvantaged areas, focusing on family engagement in physical activity and perceived changes in family dynamics. Methods A qualitative design with an ethnographic approach was employed. In line with an ethnographic approach, the research team conducted 15 participant observations of the programme sessions on Saturdays during Spring 2022. Field notes were compiled during the observations, which provided contextual information for individual interviews with 12 programme participants. These interviews were conducted after the researchers attended the programme. The participants were adults/parents who participated in the programme with one or more of their children. An inductive reflexive thematic analysis was used to analyse the field notes and interviews. Results The analysis identified three main themes: (1) prioritising children’s equal engagement in physical activity, (2) helping parents promote children’s healthy lifestyles, and (3) improving family dynamics through engagement in physical activity. Each theme captures an aspect of the programme that parents perceived as essential to facilitating their family’s engagement in the programme. All the themes are interconnected and form the basis for improving family dynamics. Conclusion To develop tailored family-based programmes in socioeconomically deprived communities, it is crucial to understand parents’ experiences and perceptions of aspects that facilitate their children’s engagement in physical activity. The findings suggest that emphasising equal opportunities, a safe space approach and participation are essential for increasing family engagement in physical activity. These elements also supported increasing parents’ awareness of their children’s need to be active and have fun together.